2014
DOI: 10.1002/j.0022-0337.2014.78.6.tb05737.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Technology for Millennial Dental Hygiene Students: A Survey of U.S. Dental Hygiene Programs

Abstract: A growing body of literature suggests that today's learners have changed and education must change as well since Millennial generation students expect technology to be used in their coursework. This study sought to determine what educational technology is being used in U.S. dental hygiene programs, what student and faculty perceptions are of the effectiveness of technology, and what barriers exist to implementing educational technology. A stratiied random sample of 120 entry-level dental hygiene programs natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…We need to provide students with clear expectations and learning and practice opportunities if we want them to succeed. Thus, in addition to the need for an attitude of openness to technology by older generations, technology training must be available to both students and faculty if we are to redefine our relationship with students as collaborative 32 …”
Section: Even Digital Natives Need Guidancementioning
confidence: 99%
“…We need to provide students with clear expectations and learning and practice opportunities if we want them to succeed. Thus, in addition to the need for an attitude of openness to technology by older generations, technology training must be available to both students and faculty if we are to redefine our relationship with students as collaborative 32 …”
Section: Even Digital Natives Need Guidancementioning
confidence: 99%
“…For example, an individual can review slides on a laptop at home, then continue on a tablet while taking public transportation to school, and continue to review on a smartphone during free time at school. Integrating proven approaches to learning (spaced repetition) with technological devices that are widely used by today's learners (e.g., touch screen‐enabled mobile devices 9 , 10 ) with software that can be accessed and synchronized across multiple platforms should enhance learning. The aim of our pilot project was to evaluate and compare student perception and utilization of a mobile device‐optimized electronic oral pathology‐oral radiology database of case‐based questions for dental hygiene and dental students.…”
mentioning
confidence: 99%
“…In a study of use of Twitter as an educational tool in pharmacy, 71% of students said it was distracting because of their desire to read general content on Twitter rather than the course material 25 . In a survey of dental hygiene programs, Beebe et al found that most students and faculty members preferred a hybrid course with both online and face‐to‐face instruction, whereas only 8% or less reported that online alone was a good educational format 26 . In that study, faculty members reported that barriers to using social media for course instruction included technical difficulties and students' using the technology for non‐academic purposes during class.…”
Section: Viewpoint 2: Potential Problems With Social Media Outweigh Tmentioning
confidence: 99%